Discharge against medical advice among infants with 24–31 weeks’ gestation admitted to Chinese neonatal intensive care units: A multicenter cohort study - Xiu, Wenlong; Bai, Ruimiao; Gu, Xinyue; Jiang, Siyuan; Zhang, Baoquan; Ding, Ya; Wang, Yanchen; Liu, Ling; Sun, Jianhua; Cao, Yun; Zhou, Wenhao; Lee, Shoo K.; et al. (Frontiers in Pediatrics, 2022)
Background: Previous studies demonstrated high rates of discharge against medical advice (DAMA) among very preterm infants (VPIs) in China. Objectives: To investigate the concurrent incidence, variation, and predictors of DAMA, along with the effect of DAMA on mortality of VPIs in China using data from the Chinese Neonatal Network (CHNN). Methods: All infants born at 24 to 31 complete weeks’ gestation and admitted to 57 CHNN Neonatal Intensive Care Units (NICUs) in 2019 were included for this cohort study, excluding infants with major congenital anomalies. Patient information was prospectively collected using the CHNN database. Multivariable log-linear regression was used to assess the association of perinatal factors and DAMA. Results: A total of 9442 infants born at 24 to 31complete weeks’ gestation and admitted to 57 CHNN participating sites in 2019 were included in the study. Overall, 1341 infants (14.2%) were discharged against medical advice. Rates of DAMA decreased with increasing GA, and infants with lower GA were discharged earlier. DAMA infants had significantly higher rates of necrotizing enterocolitis, severe brain impairment, and bronchopulmonary dysplasia than non-DAMA infants. A total of 58.2% DAMA infants were predicted to die after discharge. The attributable risk percent of mortality among DAMA infants were 92.4%. Younger maternal age, lower gestational age, SGA and Apgar Score ≤3 at 5 min were independently associated with increased risk of DAMA, while infants with antenatal steroids were less likely to be DAMA. Conclusions: The rate of discharged against medical advice in preterm infants between 24 to 31 weeks’ gestation remained high in China with a significant impact on the mortality rates. Continuous efforts to reduce DAMA would result in substantial improvement of outcomes for VPIs in China.